2016
DOI: 10.1590/0037-8682-0254-2015
|View full text |Cite
|
Sign up to set email alerts
|

Ten years of a hantavirus disease emergency in the Federal District, Brazil

Abstract: Introduction: Hantavirus diseases are emerging human diseases caused by Hantavirus spp. of the Bunnyaviridae family. Hantavirus pulmonary syndrome (HPS) has been detected in the Federal District (DF) of Brazil since 2004. Among the 27 Brazilian Federal Units, DF has the highest fatality rate. More than 10 years have already passed since then, with confi rmation of cases caused by the Araraquara and Paranoa species. The reservoir is Necromys lasiurus. Methods: Local surveillance data of the confi rmed cases wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
(33 reference statements)
1
6
0
Order By: Relevance
“…This fi nding reinforces the need for public health policies and management in the FD regarding leptospirosis and other acute febrile diseases (hantavirus, yellow fever, and infl uenza) in addition to dengue fever, which are considered one of the most important public health issues in Brazil 4,15 . Despite leptospirosis having less morbidity than dengue fever in the FD, the lethality of the disease is higher than infections caused by the dengue virus 11 .…”
Section: Discussionsupporting
confidence: 57%
“…This fi nding reinforces the need for public health policies and management in the FD regarding leptospirosis and other acute febrile diseases (hantavirus, yellow fever, and infl uenza) in addition to dengue fever, which are considered one of the most important public health issues in Brazil 4,15 . Despite leptospirosis having less morbidity than dengue fever in the FD, the lethality of the disease is higher than infections caused by the dengue virus 11 .…”
Section: Discussionsupporting
confidence: 57%
“…This study corroborates the findings of Willemann & Oliveira, 12 who observed regional differences in hantavirus lethality in a case-control study with secondary data from 2007 to 2010, relating to the regions of Brazil, with the objective of evaluating risk factors for death from hantavirus. With regard to the groups most vulnerable to death from hantavirus, in a descriptive study conducted in Brazil's Distrito Federal between 2004 and 2013, Dusi et al 13 also found higher lethality in females than in males. Menezes et al, 14 in a cross-sectional study conducted in the state of Goias between 2007 and 2013, and Kaya et al, 15 in a review on prognostic factors for hantavirus infection, also identified higher lethality in most vulnerable age groups -such as children -as well as in other groups traditionally considered to be less exposed to infection.…”
Section: Discussionmentioning
confidence: 98%
“…The outbreaks in São Paulo and DF were due to the deforestation of rodents' native habitats (Ferreira, 2003). Among the 27 Brazilian federative units, DF has the highest fatality rate (Dusi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, efforts to detect disease outbreaks should also focus on analyzing the influence of disturbed landscapes, primarily, agricultural areas (Goodin et al, 2006). Dusi et al (2016) described the main epidemiological aspects of hantavirus cases in the DF during the period 2004−2013, including field surveillance of age, sex, month and year of occurrence, clinical symptoms, syndromes and outcomes, and probable transmission place. In this period, the authors found 126 cases of hantavirus, predominantly from April (end of wet season) to August (peak of dry season).…”
Section: Introductionmentioning
confidence: 99%